Building the Resilience of WSS Utilities to Climate Change and Other Threats : A Road Map - World Bank Group (World Bank, Washington, DC, 2019)
Water supply and sanitation (WSS) utilities are expected to become increasingly susceptible to the expected impacts of climate change. WSS utility planners and engineers have dealt with natural climate variances and disaster planning as part of the design process for many years. However, the traditional methods for these plans have not considered the deep uncertainty surrounding many future conditions, which are further exacerbated by climate change. To help utilities incorporate resilience and robustness in their choices, this road map proposes a process in three phases that can inform the design of strategies necessary to WSS services provision. The road map builds on the understanding that climate change is most often an amplifier of existing uncertainties (many of which are threats), and, as such, should not be evaluated as a stand-alone impact. The approach reveals the strengths and vulnerabilities of investment plans concisely and helps utilities invest robustly by identifying near-term, no-regret projects that can be undertaken now, while maintaining flexibility in pursuing additional actions adaptively as future conditions evolve. These results can be achieved both with a qualitative exploration and a quantitative assessment, depending on the context and the resources available.